Building a framework for a partnership business model. (1st February 2010) - Jarvi, Kati; Sainio, Liisa-Maija; Ritala, Paavo; Pellinen, Antti
Value in the business model concept is traditionally described from the perspective of end-customers. We argue that this is not sufficient in today's competitive multichannel environment. We utilise a transactional perspective and extend the notion of exchange of value and resources to the firm's partners. The developed partnership business model construct is introduced and its usability to analyse interfirm cooperation related to provision of IP multimedia communication services is examined empirically. The goal is to find out why an operator would be a preferred channel for service delivery, and what would make their partnership business model attractive from the partners' perspective. The results suggest that partners evaluate the attractiveness of the business model of an operator in terms of value and resources. The partnership business model construct provides a valuable perspective to companies who have to consider how to attract good partners to stay competitive.